Corporate Board Gender Diversity and Performance: Evidence from Nigerian Stock Exchange - Abubakar, Bilkisu Aliyu; Garba, Tukur; Sokoto, Abubakar Abdullahi; Maishanu, Malami M. (Economic Journal of Nepal, 2014)
This study aims at investigating the relationship between corporate board gender diversityand firms’ performance. The study uses non-probability sampling method in the form ofavailability sampling technique in selecting the firms that constitute the sample for this study.To achieve the objectives of this study, pooled-ordinary least squares, fixed effects andrandom effects estimators have been applied on a panel sample of 82 firms listed on theNigerian Stock Exchange for the period 2004-2009. The findings reveal that gender diversityand board composition have significant and positive influence on firms’ financialperformance while family directorship reduces firms’ performance. The Economic Journal of Nepal, Vol. 34, No. 4, October-December 2011 (Issue N0. 136)